الجماعات غير الرسمية داخل إدارة المؤسسة التربوية وأثرها في الاغتارب الوظيفي، الثانوية نموذجا. - بوخلوه عبد الحفيظ (جامعة البليدة 2؛ كلية العلوم الانسانية والاجتماعية, 2023)
إن ما يميز العلاقات داخل المدرسة هو الحوار البناء بين أعضاء الجماعة التربوية بالواجبات المطلوبة على أكمل وجه، لأجل نجاح العملية التربوية، إلا أن كثيار من الأساتذة ممن لم يتمكنوا من القيام بالمهام الموكلة إليهم يلجؤون إلى التقرب من رؤساء العمل بشتى الوسائل ومن ذلك نقل صور قاتمة عن بقية الزملاء، ونشر الإشاعات عنهم، وتشكيل تحالفات سرية ومعلنة، كل ذلك جعل التنظيم الرسمي متمثلا في إدارة المؤسسة وبما تستند إليه من تشريعات وسلطات مخولة لها قانونا يفقد فعاليته في التحكم في السير الحسن للمؤسسة التربوية لصالح التنظيم غير الرسمي، كما أن هذه الفئة هي من ترتقي إلى المناصب العليا دون بذل أي جهد، وفي ظل ذلك أصبح الأستاذ الجاد والطموح يصاب بحالة من الإحباط والاغتارب في محيط العمل. من خلال ذلك كله جاءت هذه الدارسة والموسومة بعنوان: الجماعات غير الرسمية داخل إدارة المؤسسة التربوية وأثرها في الاغتارب الوظيفي، الثانوية نموذجا (دارسة ميدانية لمجموعة من الأساتذة المدرسين بالطور الثانوي بمدينة ورقلة) ولقد هدفت هذه الدارسة إلى ما يلي: التعرض لظاهرة وجود جماعات غير رسمية داخل الإدارة التربوية بشكل أعمق، ومحاولة  طرحها بأكثر دقة، ووصف هذه الظاهرة وصفا سليما مجردا عن أي خلفية أو أفكار مسبقة. تفسير ظاهرة الاغتارب الوظيفي من خلال الكشف عن العلاقة التي قد تكون بين وجود  جماعات غير رسمية داخل الإدارة التربوية في جوانبها السلبية والاغتارب الوظيفي. معرفة مصادر الاغتارب الوظيفي لدى أستاذ التعليم الثانوي، وأبعاده ومؤشارته.  معرفة الفروق الموجودة بين أساتذة الطور الثانوي، ومدى تأثير وجود جماعات غير رسمية  داخل الإدارة التربوية في تعرضهم للاغتارب الوظيفي، انطلاقا من تلك الفروق. ملخــــــــــــــــص الدارســــــــــــــــة باللغــــــــــــــــة العربيـــــــــــــة أما المنهج المعتمد في الموضوع الذي بين أيدينا هو المنهج التحليلي الوصفي لأنه المنهج المناسب لدارسة الظواهر الاجتماعية، وكانت العينة المختارة ل ة اس رّ لد غير احتمالية وهي (العينة 189 ولقد طبقناها على ،%26.50 حيث أخذناها من مجتمع البحث بنسبة تقارب ،)القصدية وبما أن المنهج الذي تم اعتماده في هذه ، ثانوية من ثانويات مدينة ورقلة 12 أستاذا ينتمون إلى اسة رّ الد هو منهج التحليل الوصفي فإن ذلك استلزم الاستعانة بتقنية :الاستمارة كتقنية رئيسة والمقابلة كتقنية مساعدة، ولقد دارت إشكالية الدارسة حول وجود جماعات غير رسمية داخل إدارة المؤسسة التربوية ومدى تأثي رها على الاغتارب الوظيفي لأستاذ التعليم الثانوي (الثانوية)، ولقد توصلنا من خلال هذه الدارسة إلى النتائج التالية: . لا توجد علاقة بين الحجم الساعي المكثف و الاغتارب الوظيفي لأستاذ التعليم الثانوي  أن الأستاذ يشعر بالارتياح بالانتماء لمهنة التعليم في السنوات الأولى للتدريس ثم يقل ذلك  الشعور بتقدمه في ممارسة مهنة التعليم. كما ي ز داد شعوره بالعزلة والاغتارب الوظيفي. أهم عوامل نشأة الجماعات غير الرسمية داخل الوسط الثانوي هي نوع القيادة التربوية وطريقتها  وأن القيادة الضعيفة من أهم أسباب ذلك، وهي ، بالإضافة للمصالح الشخصية ،في التسيير المسبب الأول للاغتارب الوظيفي. . تزداد حدة الاغتارب الوظيفي لدى المدرسين الأساتذة أكثر من الأستاذات  ملخص الدارسة باللغة الإ نجليزية Study Summary: What distinguishes the relations within the school is the constructive dialog between the members of the educational community for the success of the educational process, but many teachers and members of the administrative staff who were unable to carry out the tasks assigned to them resort to evading the heads of work by various means, including the transmission of gloomy pictures from the rest of the colleagues. This has made the official organization represented by the management of the institution and the legislation and powers on which it is legally empowered to lose its effectiveness in controlling the good quality of the educational institution in favor of the informal organization, and these opportunists are the ones who rise to senior positions without any effort. In this context, the serious teacher became frustrated and alienated in the work environment. Through all this came this study, which is entitled: Informal groups within the administration of the educational institution and their impact on job alienation, case of secondary school (a field study of a group of teachers in the secondary education phase in the city of Ouargla). The objectives of this study are as follows:  Tackling the phenomenon of the probable existence of informal groups within the educational administration in a deeper way, and try to deep with it, describing this phenomenon properly and without any preconceived ideas.  Explaining the phenomenon of job alienation by revealing the relationship that could be attributed to the existence of informal groups within the educational administration in its negative aspects and job alienation.  Recognizing the sources of job alienation in the teacher of secondary education, its dimensions and indicators.  Highlighting the differences between secondary school teachers and the extent to which the presence of informal groups within the educational administration affects their knowledge of job alienation, based on these differences. The method adopted in the study is the analytical-descriptive method because it is the most appropriate approach to study social phenomena, and the sample chosen for the study was (purposeful sample), and was the total of teaching at the secondary stage in Ouargla, Algeria, where we took the sample from the research community by about 26.50% of teachers, we applied it to 89 teachers belonging ملخــــــــــــــــص الد راســــــــــــــــة باللغــــــــــــــــة الإنجليزيـــــــــــــة to 12 high schools in Ouargla using the following technology: Investing as a key technique and interviewing as an assistive technique. The research problem circulates around: The existence of informal groups within the administration of the educational institution on the job alienation of teachers within the secondary education institution. Upon this, the following findings have been concluded:  There is no relationship between the intense hourly volume and the job alienation of secondary education teachers.  The teacher is satisfied with belonging to the profession of education downgrades from their early years during their progress in the practicing he profession of education. They are also increasingly feeling alienated.  Job alienation among male-teacher is more acute than among femaleteachers.  The most significant factors in the formation of informal groups within the secondary environment are the type of educational leadership and its way of conducting, in addition to personal interests, because vulnerable leadership is one of the most important reasons for this to happen, and it is also the reason of job alienation.
(دارسة ميدانية لمجموعة من الأساتذة المدرسين بالطور الثانوي بمدينة ورقلة)
Keywords: الجماعات الغير رسمية; المؤسسة التربو; ية